Study of modal properties and crashworthiness performance of crash box numerical model with different joining modelling strategies - N.A.Z., Abdullah; M. S. M., Sani; Salwani, Mohd Salleh (IOP Publishing, 2021)
It is important to understand the natural frequencies and the mode shapes for automotive structure such as crash box as it will be subjected to the dynamic loading in its real application. In addition, it is also important to study other dynamic behaviour such as crash and buckling as crash box is one of energy absorbing member that is intended for car safety during collision. In this study, modal properties of three different crash box models joint by three different joint modelling strategies and also their crash and buckling behaviour was analysed and investigated. Computational frequency analysis, dynamic crash analysis and nonlinear buckling analysis was performed on all of crash box models. the crash box modelled with node equivalent method to represent the welded joint shows higher stiffness at the joining area and therefore shows higher value of natural frequencies that the model with CBEAM and CBAR elements as their joining elements. In term of crash behaviour, the model with CBEAM element shows higher reaction force compared to the CBEAM. This proves that different type of joint modelling strategies behaves differently.